SHM_415340_HST_3D Polygonal Stone Axe - Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of an Early Neolithic polygonal stone axe collected from Skåne and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=694

Link to Sök I Samlingarna

https://samlingar.shm.se/object/9093CDFD-7ED0-4AC4-9F54-44670BBCD57D
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Swedish Early Neolithic; Dynamic Collections; Archaeology/history; History and archaeology; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi